The effect of NIKKEI and crude oil on market indices during COVID-19 in Indonesia - Dila Anike Pagora; Inka Sefrani Supu; Prisilia Yulia Memah; Rosiyani Manangkabo (Yayasan Widyantara Nawasena Raharja, 2023)
Several world economic indicators that are interrelated and affected by the COVID-19 pandemic are IHSG, NIKKEI, and the world oil price. The sample of this study is taken from 9 June 2020 to 7 June 2021 in objective to analyze the impact of oil price and NIKKEI on IHSG. This study finds that increasing in oil prices and the NIKKEI have significant positive impact on the IHSG on the Indonesia Stock Exchange. This study indicates that the COVID-19 pandemic does not always result for negative impact on world economy. Moreover, the movement of the market index tends to be responded positively by investors which indicate optimism about economic growth in Indonesia.